An Analysis of Teacher Questions and Student Responses in the Teaching and Learning Process - Marita, Yosi; Ediah Yusti Mulyansari (Corolla International Conference, 2022)
The research aims to analyze teacher inquiries and student responses in the teaching and learning process to determine how interactions in the classroom between teachers and students affect how effectively lessons are taught and learned. Students and teachers both play important roles in the class. The teacher is among the crucial elements that affect how well students learn and retain information. Since the students are the ones who are actually learning the material in the classroom, the teacher is the source of input. In everyday conversation, particularly in the classroom, asking questions is important. Far more frequently than higher-level questions that invite students to consider their knowledge, factual tests to gauge students' comprehension of fundamental concepts are used. Direct observation was used to gather the data in order to categorize the different kinds of student responses—whether they were nonverbal, written, or oral—in the observation checklist. The analysis's findings indicated that the dominant response was eye contact (18.1%). because responses indicated by eye contact to the lecturers' questions that there was interaction between them. Incorporate guidance, practice, and feedback into structured lessons by giving students immediate feedback on a problem, question, or calculation. Keywords: Questions, Responses, Teaching, Learning, Classroom